2012
DOI: 10.1128/aem.01792-12
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Assessment of the Kinetics of Hg-Cell Association, Hg Methylation, and Methylmercury Degradation in Several Desulfovibrio Species

Abstract: . We tested the hypothesis that differences in Hg(II) i sorption and/or uptake rates drive observed differences in methylation rates among Desulfovibrio species. Hg(II) i associated rapidly and with high affinity to both methylating and nonmethylating species. MeHg production by Hg-methylating strains was rapid, plateauing after ϳ3 h. All MeHg produced was rapidly exported. We also tested the idea that all Desulfovibrio species are capable of Hg(II) i methylation but that rapid demethylation masks its producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
126
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(139 citation statements)
references
References 62 publications
12
126
1
Order By: Relevance
“…Further, Hgmethylating SRB and FeRB appear to sorb lower amounts of Hg than do non-methylating strains. 17 14…”
Section: Methylation Was Variable Among the Firmicutes Although Fementioning
confidence: 98%
“…Further, Hgmethylating SRB and FeRB appear to sorb lower amounts of Hg than do non-methylating strains. 17 14…”
Section: Methylation Was Variable Among the Firmicutes Although Fementioning
confidence: 98%
“…Certain 96 bacterial strains such as Geobacter sulfurreducens PCA can function both as a reductant and as 97 an adsorbent for Hg(II) at different cell biomass to Hg ratios (Hu et al, 2013), with adsorption 98 being the dominant mechanism at low Hg:biomass ratios. Sorption of Hg(II) to cell envelope 99 sites has been thought to serve as a "sink" for Hg(II) that restricts transport into the cytoplasm, 100 thus lowering the bioavailability of Hg(II) (Graham et al, 2012). Recent studies indicate that in 101 addition to gene expression and regulation, cell envelope chemistry is likely an important driver 102 for cross-species differences in Hg methylation rates (Graham et al, 2012).…”
mentioning
confidence: 99%
“…Sorption of Hg(II) to cell envelope 99 sites has been thought to serve as a "sink" for Hg(II) that restricts transport into the cytoplasm, 100 thus lowering the bioavailability of Hg(II) (Graham et al, 2012). Recent studies indicate that in 101 addition to gene expression and regulation, cell envelope chemistry is likely an important driver 102 for cross-species differences in Hg methylation rates (Graham et al, 2012). Furthermore, 103 reactivity of thiols towards Hg(0), resulting in thiol mediated passive microbial oxidation of 104 Hg(0), has been recently reported (Colombo et al, 2013; Colombo et al, 2014).…”
mentioning
confidence: 99%
“…Gilmour et al [38] indicate that over 50 % of the Desulfovibrio strains tested have the capability of producing methylmercury. From a study involving 59 species of Desulfovibrio, Graham et al [39] determined that mercury methylation is species-specific and is not restricted to a given phylogeny. Recently, it was shown that for the mercury methylation process in D. desulfuricans ND132, genes hgcA and hgcB are required [72].…”
Section: Hg(ii)mentioning
confidence: 98%